Stage-Dependent Within-Individual Comparison Reveals SIV-Specific Activation/Exhaustion Shift in Rhesus Macaques - Tong, Ling; Cong, Zhe; Tian, Long; Zhang, Jingjing; Lu, Jiahan; Lu, Qiuhan; Chen, Ting; Wang, Yuhong; Wei, Qiang; Xue, Jing (Frontiers in Microbiology, 2021)
It is challenging to trace the complicated individual-based variations of HIV-specific immunocompetence shift during the successful antiretroviral therapy (ART) era. Using eight rhesus monkeys simulating a longitudinal stage-dependent cohort (baseline-SIV acute infection-SIV suppression by ART-ART withdrawal), baseline immunocompetence monitoring for 28 days (SIV-negative stage, SN) was compared with host immunocompetence undergone 90-days ART treatment (SIV-suppressed stage, SS) to reveal the SIV-specific immunity shift aroused by undetectable individual viral replication. During acute SIV infection for 98 days (SIV-emerged stage, SE), immune activation was compared with re-immune activation post ART for 49-day follow-up (SIV-rebounded stage, SR) to reveal the SIV-specific immune activation variation aroused by detectable individual viral replication. Individual immunocompetence was measured by co-expression of CD4, CD8, CD38, HLA-DR, CCR7, CD45RA, PD-1 on T cells and a cytokines panel. Compared with SN, mild immune activation/exhaustion was characterized by increased CD38+ HLA-DR− CD4+/CD8+ T-cell subsets and PD-1+ memory CD4+/CD8+ T-cell subsets with three elevated cytokines (MIP-1β, IL-8, and IL-10) significantly emerged in SS. Compared with SE, SR produced more exhaustion characterized by increased PD-1+ CD4+ TCM cells, decreased PD-1+ CD4+ TEM cells with four elevated pro-inflammatory cytokines (IFN-γ, IL-1β, IL-6, and TNF-α). By such individualized stage-dependent comparison, the sustainable immune activation was found from activation/exhaustion shifted into exhaustion during the longitudinal viral persistence. Further, validated HIV accelerates host immunosenescence continuously independent of viral replication.